The lost quilter : an Elm Creek quilts novel - Chiaverini, Jennifer (New York : Simon & Schuster, 2009)
Master quilter Sylvia Compson investigates her ancestry and discovers unexpected connections to a runaway slave and quilter who traveled the Underground Railroad to Elm Creek Farm before she was captured and returned to Virginia.
Keywords: Compson, Sylvia (Fictitious character) -- Fiction; Quilting -- Fiction; Quiltmakers -- Fiction; Quilts -- Fiction; Genealogy -- Fiction; Domestic fiction